Preparation method of low-cost high-heat-resistance microwave composite dielectric plate
Patent Information
- Application Number
- CN202611013021.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-08
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]本发明针对目前市售碳氢树脂、PPO、PI材料微波复合介质板耐热性能差、吸水率高、直接采用陶瓷先驱体价格昂贵工艺不成熟的问题,目的在于提供沿用传统介质板生产流程和设备、高耐热、低成本的新型微波复合介质板的制备方法,性能好、成本低、设备简单、操作方便、可大规模应用
[0040]第一,本发明中制备得到的微波复合介质板表现出比现有商业产品更优异的适用性能:
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of microwave composite dielectric substrate manufacturing technology, and in particular to a method for preparing a low-cost, high-heat-resistant microwave composite dielectric substrate. Background Technology
[0002] Modern electronic equipment is developing towards integration, miniaturization, lightweighting, and high mobility. Previously, low-power chip-integrated microwave components could no longer meet design requirements. High-power microwave transducer (TR) chips with higher integration are gradually being used in weaponry, significantly increasing the heat dissipation requirements for microwave components. In particular, the application and promotion of SIP-based TRs and RF front-end technologies have led to increasingly higher power and single-point heat flux densities for devices integrated on microstrip boards. Traditional microwave composite dielectric boards are poor conductors of heat. Microwave dielectric boards based on hydrocarbon resin and PPO, such as RO4350B and MEGTRON 6, widely used in 5G networks as antennas, have a long-term operating temperature ≤200℃ and Td (5%) ≤400℃, which cannot meet the requirements for higher integration and greater power consumption.
[0003] Currently, improving the heat resistance of microstrip boards mainly relies on thermal control systems, using methods such as air cooling and water cooling to achieve forced convection and remove local heat. However, when the external working environment is continuously high-temperature, the microstrip board cannot withstand the high temperature independently, limiting its application in this type of field. Furthermore, with high-temperature environments, the risks from humid heat also increase exponentially. Although copper-clad laminates based on PI can achieve a Td (5%) ≥ 500℃, their high water absorption and significant decrease in dielectric properties at high temperatures also make them unsuitable for high-temperature environments.
[0004] Ceramic precursors, as novel materials for ceramic preparation, allow for some control over product composition through molecular design. Their mild preparation conditions make them particularly advantageous in the fabrication of continuous ceramic fibers, thin films, composite materials, and coatings. They have already found applications as coatings with special functions such as hardening, wear resistance, and corrosion protection. However, there are no precedents, either domestically or internationally, for using ceramic precursors in microwave composite dielectric substrates. Furthermore, ceramic precursors are expensive and reactive, readily reacting with water, polar compounds, and oxygen, posing significant cost pressures and requiring substantial changes to the fabrication process for direct use in microwave composite dielectric substrates. Therefore, finding a high-heat-resistant, low-cost method for preparing microwave composite dielectric substrates based on ceramic precursors, while utilizing traditional dielectric substrate production processes and equipment, is a pressing issue. Summary of the Invention
[0005] This invention addresses the problems of poor heat resistance, high water absorption, and high cost and immature process of using ceramic precursors in commercially available microwave composite dielectric boards made of hydrocarbon resin, PPO, and PI. The aim is to provide a novel method for preparing microwave composite dielectric boards that uses traditional dielectric board production processes and equipment, has high heat resistance, and low cost. This method offers good performance, low cost, simple equipment, convenient operation, and can be applied on a large scale.
[0006] To achieve the above objectives, the present invention provides a method for preparing a low-cost, high-heat-resistant microwave composite dielectric substrate, comprising the following steps:
[0007] S1: Preparation of semi-cured impregnated sheets based on diene resin;
[0008] S2: A ceramic precursor adhesive is coated on the surface of the semi-cured impregnated sheet to form an adhesive layer;
[0009] S3: Stack the coated impregnated sheets;
[0010] S4: Place metal foils on the top and bottom layers after stacking, and vacuum press them in a high-temperature laminator to obtain a microwave composite dielectric board.
[0011] Preferably, in step S1, the method for preparing the semi-cured impregnated sheet includes:
[0012] S11: Mix the raw materials for impregnating sheet solution in a high-shear mixing tank according to the specified proportion;
[0013] S12: The impregnating sheet adhesive obtained in S11 is mixed with electronic fiberglass cloth in a gluing machine to form a continuous roll of impregnating sheet, and then dried to form a roll of semi-cured impregnating sheet.
[0014] S13: Cut the roll of the semi-cured impregnated sheet obtained in S12 into impregnated single sheets that match the size of the microwave composite dielectric plate.
[0015] Preferably, in step S11, the impregnating sheet adhesive is made from the following raw materials in parts by weight: 100 parts diene resin, 10-60 parts thermoplastic elastomer toughening resin, 10-40 parts liquid toughening agent, 20-70 parts ceramic filler, 0.01-1.5 parts coupling agent, 0.05-5 parts hydrolyzed solvent, 0.5-6 parts curing agent for impregnating sheets, 0.5-20 parts additives, and 50-200 parts solvent for impregnating sheets.
[0016] Preferably, the diene resin is one or more of butadiene resin, pentadiene resin, isoprene resin and hexadiene resin;
[0017] The thermoplastic elastomer toughening resin is one or more of styrene-butadiene copolymer, styrene-isoprene copolymer, ethylene propylene diene monomer copolymer, and thermoplastic polyurethane;
[0018] The liquid toughening agent is one or more of polyurethane liquid rubber, polybutadiene liquid rubber, isoprene liquid rubber and EPDM liquid rubber.
[0019] The ceramic filler is one or more of the following: crystalline silica, fused silica, spherical silica, hollow microsphere silica, rutile titanium dioxide, anatase titanium dioxide, hollow microsphere titanium dioxide, alumina, hollow microsphere alumina, and hollow microsphere aluminum nitride; the median particle size of the ceramic filler is 10 μm to 30 μm.
[0020] The coupling agent is one or more of Z-6040, Z-6124, Z-6030 and KH550 in combination;
[0021] The curing agent for the impregnated sheet is one or more of peroxide initiators, vulcanizing crosslinking agents and triallyl cyanurate crosslinking agents;
[0022] The solvent used for the impregnated sheet is one or more of the following: water, 1,2-propanediol, dichloromethane, ethanol, xylene, and cyclohexane.
[0023] Preferably, the specific steps of S11 are as follows:
[0024] S111: After the coupling agent is pretreated with a hydrolytic solvent, the ceramic filler and the hydrolyzed coupling agent are added to a planetary ball mill in proportion and ball-milled at 60℃~90℃ for 1h~2h. The mixture is then removed and set aside for use.
[0025] S112: Diolefin resin, thermoplastic elastomer toughening resin and impregnated sheet are added to a high-shear stirring tank with solvent, and stirred for 3 to 6 hours at a temperature of 50℃~90℃ and a stirring speed of 100r / min~600r / min. The mixture is then removed and set aside for use.
[0026] Add the products of S111 and S112 to a high-shear mixing vessel, and then add liquid toughening agent, curing agent and additives in proportion. The mixing temperature is 60℃~95℃, the mixing speed is 100r / min~1000r / min, and the mixing time is 50min~180min. During the process, the vacuum degassing mode is turned on.
[0027] Preferably, the specific steps of S12 are as follows:
[0028] S121: The electronic fiberglass cloth is impregnated in the impregnation solution after S11 treatment under vacuum-assisted conditions. The mass concentration of the solution is 10% to 80%. The impregnation is repeated 2 to 5 times, and the thickness is adjusted to the predetermined thickness according to the type of electronic fiberglass cloth.
[0029] S122: Dry the impregnated electronic fiberglass cloth at 100-150℃ for 2-5 minutes to remove low-temperature volatiles and form a semi-cured state, thus obtaining the roll of the semi-cured impregnated sheet.
[0030] Preferably, the electronic fiberglass cloth is one of electronic grade low dielectric alkali-free fiberglass cloths of 106, 1080, 1067, 2116 and 7628, and the thickness of the electronic fiberglass cloth is less than 0.03 mm.
[0031] Preferably, in step S2, the specific operation of coating the ceramic precursor adhesive to form the adhesive layer is as follows: a coating unit with a five-roll structure is used to coat the film, and the thickness of the adhesive layer coated on one side is 5μm to 13μm; after coating, the impregnated sheet is treated in a drying oven at 80℃ to 110℃ for 0.5 to 3 hours, and then cooled for 10 minutes to 30 minutes.
[0032] Preferably, the ceramic precursor adhesive is made from the following raw materials in parts by weight: 100 parts of ceramic precursor and its modified resin, 0.5 to 2 parts of curing agent for adhesive layer, 60 to 250 parts of solvent for adhesive layer, 10 to 60 parts of ceramic microspheres and 0.1 to 1.5 parts of surface modifier;
[0033] The ceramic precursor and its modified resin are one or more of the following: perhydropolysilazane, polyvinylsilazane, and block copolymer modified polysilazane;
[0034] The ceramic microspheres are one or more of silicon carbide, boron carbide and silicon oxide; the median particle size of the ceramic microspheres is 0.5 μm to 2 μm.
[0035] The surface modifier is one or more of Z-6040, Z-6124 and Z-6030 in combination;
[0036] The curing agent for the adhesive layer is one or more of toluene diisocyanate, dicumyl peroxide, and ethylene dithiol;
[0037] The solvent used in the adhesive layer is one or more of the following: hexane, toluene, xylene, dichloromethane, butanone, tetrahydrofuran, cyclohexane, 1,2-propanediol, and bromophenyl ether.
[0038] Preferably, the preparation method of the ceramic precursor adhesive is as follows: the ceramic precursor and its modified resin, the curing agent for the adhesive layer and the solvent for the adhesive layer are added to a planetary ball mill in proportion, and the mill is run alternately in forward and reverse directions at a speed of 200 r / min to 350 r / min at 40℃ to 60℃ for 30 min to 180 min, and the circulating water cooling is turned on during the ball milling process.
[0039] Compared with related technologies, the method for preparing a low-cost, high-heat-resistant microwave composite dielectric plate provided by the present invention has the following advantages:
[0040] First, the microwave composite dielectric substrate prepared in this invention exhibits superior applicability compared to existing commercial products:
[0041] 1. Improved heat resistance: This product can be used continuously for a long time in high-temperature environments of 250℃~280℃, which is more than 50℃ higher than existing products. It is suitable for millimeter-wave devices such as antenna systems, correction networks, and power dividers in high-power electronic information equipment.
[0042] 2. Higher strength and machinability: The pencil hardness of this product can be ≥6H, which is 30% higher than that of existing products, providing better support and machinability and reliability for the assembly of highly integrated microwave devices and antenna elements.
[0043] 3. Low cost: The cost of this product is ≤5% higher than that of existing products, and more than 85% lower than that of high heat-resistant microwave composite dielectric boards with pure ceramic precursors.
[0044] Secondly, this invention follows the mature impregnation-pressing process route, without the need to change the main equipment and core process conditions of the existing production line. The process parameters are easy to control and the product quality is stable. The preparation process is environmentally friendly, the equipment occupies a small area and has low production costs. It can be directly connected to the existing dielectric board production system and is easy to achieve large-scale mass production. Attached Figure Description
[0045] Figure 1 This is a complete process flow diagram of the present invention;
[0046] Figure 2 This is a process flow diagram of the preparation of the impregnation sheet adhesive solution according to the present invention;
[0047] Figure 3 This is a process flow diagram for preparing the ceramic precursor adhesive solution according to the present invention. Detailed Implementation
[0048] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that the embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Improvements and adjustments made by those skilled in the art based on the present invention in practical applications still fall within the scope of protection of the present invention.
[0049] The present invention discloses a method for preparing a low-cost, high-heat-resistant microwave composite dielectric substrate, the overall process of which is as follows:
[0050] (I) Preparation of semi-cured impregnated sheets: Using diene resin as the matrix, the impregnated sheet adhesive solution is first prepared. The coupling agent is first hydrolyzed and pretreated. The hydrolyzed coupling agent is mixed with ceramic filler and ball-milled at 60℃~90℃ for 1~2h to obtain filler premix. Then, the diene resin, thermoplastic elastomer toughening resin and other solid raw materials are added to the impregnated sheet solvent in a high-shear stirring tank and stirred at 50℃~90℃ and 100~600r / min for 3~6h to obtain resin premix. The filler premix and resin premix are mixed, and liquid toughening agent, impregnated sheet curing agent and additives are added. The mixture is stirred at 60℃~95℃ and 100~1000r / min for 50~180min. Vacuum degassing is turned on during the process to finally obtain a uniform impregnated sheet adhesive solution. The hydrolysis solvent is one or a mixture of water and ethanol, and the additives are one or a mixture of antioxidants, diluents, and pH adjusters, used to adjust the storage stability and processing performance of the adhesive solution. During the process of conveying the impregnating sheet adhesive solution to the coating machine, the bottom of the coating machine's trough is equipped with an ultrasonic dispersion device, and a replenishing adhesive cylinder is also provided. Under high-speed stirring, the impregnating sheet adhesive solution is continuously replenished to the trough at a set speed to ensure the stability of the impregnating sheet adhesive solution in the trough and to avoid sedimentation or concentration changes affecting product consistency.
[0051] (II) Impregnation and Drying: The electronic fiberglass cloth (selectable models 106, 1080, 1067, 2116, 7628, thickness <0.03mm) is impregnated in the above-mentioned impregnation sheet solution under vacuum assistance. The concentration of the impregnation sheet solution is controlled at 10% to 80%. The electronic fiberglass cloth is impregnated 2 to 5 times according to its thickness to adjust to the target thickness. Then, the impregnated electronic fiberglass cloth is sent into an oven at 100 to 150°C and dried for 2 to 5 minutes to remove low-temperature volatiles and allow the resin to reach a semi-cured state, resulting in a roll of semi-cured impregnated sheet. Finally, it is cut into impregnated single sheets that match the size of the target medium board, such as 609mm*457mm, 406mm*457mm, etc.
[0052] (III) Coating the ceramic precursor adhesive layer: First, prepare the ceramic precursor adhesive solution. Mix the ceramic precursor and its modified resin (weight average molecular weight 0.2-1.5 million, wherein the ceramic precursor is mainly perhydropolysilazane, and the modified resin is organopolysilazane, with modified groups including CH=CH2, CH3, NH, block copolymers, etc.), the adhesive layer curing agent, and the adhesive layer solvent in proportion, add them to a planetary ball mill, and stir alternately in both forward and reverse directions at a speed of 200-350 r / min at 40℃-60℃ for 30-180 min. During the process, turn on the circulating water cooling to prevent local overheating, and obtain a uniform ceramic precursor adhesive solution. The adhesive layer curing agent can be one or more of toluene diisocyanate, dicumyl peroxide, and ethylene dithiol, and the adhesive layer solvent can be one or more of n-hexane, toluene, xylene, dichloromethane, butanone, tetrahydrofuran, cyclohexane, and bromophenyl ether.
[0053] (iv) Coating and drying: Fix the cut impregnated sheet onto the carrier film, and use a five-roller coating unit to transfer the above-mentioned ceramic precursor adhesive onto the surface of the impregnated sheet. The thickness of the coating on one side is controlled at 5-13 μm. After coating, send the impregnated sheet into a drying oven at 80-110°C for 0.5-3 hours to remove the solvent for the adhesive layer. Then cool for 10-30 minutes to complete the preparation of the adhesive layer.
[0054] (v) Lamination and pressing: According to the thickness of the target dielectric substrate, the impregnated single sheets coated with the adhesive layer are laminated. Metal foil (one or more of copper, brass, aluminum, and nickel can be selected) is placed on the top and bottom layers of the laminated structure. Then, it is sent to a high-temperature laminator for vacuum pressing. Specifically, it is vacuum hot-pressed for 2 to 6 hours at 180℃~250℃ and 800~1100psi to complete the curing and finally obtain the low-cost high heat-resistant microwave composite dielectric substrate.
[0055] Example 1:
[0056] Step (1): Prepare the impregnation sheet solution according to the components specified in Example 1 in Table 1 and the process flow: First, 0.03 parts of coupling agent Z-6040 is pretreated with 0.08 parts of hydrolytic solvent and then added to a planetary ball mill with 30 parts of crystalline silica (D50=12μm). The mixture is ball-milled at 60°C for 1 hour to obtain the filler premix.
[0057] Then, 100 parts of butadiene resin, 40 parts of styrene-butadiene copolymer and 50 parts of impregnated sheet were added to a high-shear stirring tank with solvent water and stirred at 100 r / min and 60℃ for 6 h to obtain resin premix;
[0058] Mix the filler premix with the resin premix, add 10 parts isoprene liquid rubber, 3 parts peroxide initiator, and 0.5 parts additives, and stir at 60℃ and 100r / min for 180min, with vacuum degassing mode activated during the process.
[0059] Step (2): Transfer the impregnating sheet adhesive solution into the material tank, with ultrasonic dispersion at the bottom of the tank. Impregnate 106 fiberglass cloth in a uniform adhesive solution with a mass concentration of 30% under vacuum-assisted conditions, repeating the impregnation 5 times until the predetermined thickness is achieved. Dry the impregnated fiberglass cloth at 150℃ for 5 minutes to remove low-temperature volatiles and form a semi-cured state. Then, cut and repackage the semi-cured roll of impregnated sheet.
[0060] Step (3): Prepare the adhesive layer solution according to the components specified in Example 1 in Table 1: Add 100 parts of perhydropolysilazane, 20 parts of silicon carbide (D50=0.5μm), 0.3 parts of coupling agent Z-6040, 0.5 parts of toluene diisocyanate and 60 parts of dichloromethane to a planetary ball mill, and run it alternately in forward and reverse directions at 200r / min at 40℃ for 180min. Turn on the circulating water cooling during the ball milling process.
[0061] Step (4): Fix the semi-cured impregnated sheet obtained in step (2) of Example 1 onto the carrier film, and use a five-roll coating unit to coat the ceramic precursor adhesive onto the surface of the semi-cured impregnated sheet. The coating thickness on one side is 13 μm. After coating, it is processed in a drying oven with the oven temperature set at 110°C for 3 hours, followed by cooling in a cooling section for 30 minutes.
[0062] Step (5): Ten impregnated sheets obtained in step (4) of Example 1 are stacked as basic units, and then 35μm electrolytic copper foils are placed on the top and bottom layers. Vacuum pressing is performed in a high-temperature laminator. The pressing conditions are hot pressing at 250℃ and 800psi for 5 hours.
[0063] Example 2:
[0064] Step (1): Prepare the impregnation sheet solution according to the components specified in Example 2 in Table 1 and the process flow: First, 0.1 parts of coupling agent Z-6040 and 0.1 parts of Z-6124 are pretreated with 1 part of hydrolytic solvent and then added to a planetary ball mill with 40 parts of alumina (D50=15μm). The mixture is ball-milled at 80°C for 2 hours to obtain the filler premix.
[0065] Then, 100 parts of pentadiene resin, 20 parts of ethylene propylene diene copolymer and 150 parts of impregnated sheet were added to a high-shear stirring tank with solvent (water: ethanol = 8:2) and stirred at 400 r / min and 80℃ for 4 h to obtain resin premix.
[0066] Mix the filler premix with the resin premix, add 20 parts of polybutadiene liquid rubber, 5 parts of triallyl cyanurate crosslinking agent, and 1 part of additive, and stir at 80℃ and 800r / min for 70min, with vacuum degassing mode activated during the process.
[0067] Step (2): Transfer the impregnating sheet adhesive solution into the material tank, with ultrasonic dispersion at the bottom of the tank. Impregnate 2116 fiberglass cloth in a uniform adhesive solution with a mass concentration of 60% under vacuum-assisted conditions, repeating the impregnation three times to adjust to the predetermined thickness. Dry the impregnated fiberglass cloth at 130℃ for 2 minutes to remove low-temperature volatiles and form a semi-cured state. Then, cut and repackage the semi-cured roll of impregnated sheet.
[0068] Step (3): Prepare the adhesive layer solution according to the components specified in Example 2 in Table 1: Add 100 parts of polyvinylsilazane, 40 parts of boron carbide (D50=1μm), 0.1 parts of coupling agent Z-6124, 1 part of dicumyl peroxide, and 100 parts of methyl ethyl ketone to a planetary ball mill, and run it at 50°C at a speed of 250 r / min, alternating between forward and reverse rotation, and stir for 60 min. Turn on the circulating water cooling during the ball milling process.
[0069] Step (4): Fix the semi-cured impregnated sheet obtained in step (2) of Example 2 onto the carrier film, and use a five-roll coating unit to coat the ceramic precursor adhesive onto the surface of the semi-cured impregnated sheet. The coating thickness on one side is 8 μm. After coating, it is processed in a drying oven with the oven temperature set to 100°C and the processing time being 2 hours. Then, it is cooled in a cooling section for 20 minutes.
[0070] Step (5): Eight impregnated sheets obtained in step (4) of Example 2 are stacked as basic units, and then 35μm electrolytic copper foils are placed on the top and bottom layers. Vacuum pressing is performed in a high-temperature laminator. The pressing conditions are hot pressing at 220℃ and 900psi for 3 hours.
[0071] Example 3:
[0072] Step (1): Prepare the impregnation sheet solution according to the components specified in Example 3 in Table 1 and the process flow: First, 1 part of coupling agent Z-6030 is pretreated with 5 parts of hydrolytic solvent and then hydrolyzed. Then, it is added to a planetary ball mill with 60 parts of hollow microsphere silica (D50=20μm) and ball-milled at 90℃ for 1h to obtain filler premix.
[0073] Then, 100 parts of isoprene resin, 60 parts of styrene-isoprene copolymer and 200 parts of impregnated sheet were added to a high-shear stirring tank with solvent (water: ethanol = 8:2) and stirred at 600 r / min and 90℃ for 3 h to obtain resin premix;
[0074] Mix the filler premix with the resin premix, add 30 parts of EPDM liquid rubber, 3 parts of vulcanizing crosslinking agent, and 10 parts of additives, and stir at 95℃ and 1000r / min for 50min, with vacuum degassing mode activated during the process.
[0075] Step (2): Transfer the impregnating sheet adhesive solution into the material tank, with ultrasonic dispersion at the bottom of the tank. Impregnate 7628 fiberglass cloth in a uniform adhesive solution with a mass concentration of 75% under vacuum-assisted conditions, twice, adjusting to the predetermined thickness. Dry the impregnated fiberglass cloth at 110℃ for 2 minutes to remove low-temperature volatiles and form a semi-cured state. Then, cut and repackage the semi-cured roll of impregnated sheet.
[0076] Step (3): Prepare the adhesive layer solution according to the components specified in Example 3 in Table 1: Add 100 parts of block copolymer modified polysilazane, 50 parts of silica (D50=2μm), 1 part of coupling agent Z-6030, 2 parts of ethylenedithiol and 150 parts of cyclohexane to a planetary ball mill, and run it alternately in forward and reverse directions at 350r / min at 60℃ for 40min. Turn on the circulating water cooling during the ball milling process.
[0077] Step (4): Fix the semi-cured impregnated sheet obtained in step (2) of Example 3 onto the carrier film, and use a five-roll coating unit to coat the ceramic precursor adhesive onto the surface of the semi-cured impregnated sheet. The coating thickness on one side is 5 μm. After coating, it is processed in a drying oven with the oven temperature set to 90°C and the processing time being 0.5 h. Then, it is cooled in a cooling section for 10 min.
[0078] Step (5): Nine impregnated sheets obtained in step (4) of Example 3 are stacked as basic units, and then 35μm electrolytic copper foil is placed on the top and bottom layers. Vacuum pressing is performed in a high-temperature laminator. The pressing conditions are hot pressing at 250℃ and 800psi for 2 hours.
[0079] Example 4:
[0080] Step (1): Prepare the impregnation sheet solution according to the components specified in Example 4 in Table 1 and the process flow: First, 0.5 parts of coupling agent KH550 are pretreated with 0.1 parts of hydrolytic solvent and then added to a planetary ball mill with 30 parts of rutile titanium dioxide. The mixture is ball-milled at 70°C for 1.5 hours to obtain the filler premix.
[0081] Then, 100 parts of hexadiene resin, 40 parts of thermoplastic polyurethane and 100 parts of impregnated sheets were added to a high-shear stirring vessel with a solvent (water: ethanol = 8:2) and stirred at 500 r / min and 70℃ for 5 h to obtain a resin premix.
[0082] Mix the filler premix with the resin premix, add 15 parts of polyurethane liquid rubber, 1 part of peroxide initiator, 1 part of triallyl cyanurate crosslinking agent and 15 parts of additives, and stir at 85℃ and 900r / min for 100min, with vacuum degassing mode activated during the process.
[0083] Step (2): Transfer the impregnating sheet adhesive solution into the material tank, with ultrasonic dispersion at the bottom of the tank. Impregnate 1080 fiberglass cloth in a uniform adhesive solution with a mass concentration of 50% under vacuum-assisted conditions, repeating the impregnation 4 times to adjust to the predetermined thickness. Dry the impregnated fiberglass cloth at 120℃ for 3 minutes to remove low-temperature volatiles and form a semi-cured state. Then, cut and repackage the semi-cured roll of impregnated sheet.
[0084] Step (3): Prepare the adhesive layer solution according to the components specified in Example 4 in Table 1: Add 80 parts of polyvinylsilazane, 20 parts of block copolymer modified polysilazane, 10 parts of silicon carbide (D50=0.5μm), 30 parts of silicon oxide (D50=2μm), 0.5 parts of coupling agent Z-6124, 1 part of toluene diisocyanate and 80 parts of 1,2-propanediol to a planetary ball mill, and run it alternately in forward and reverse directions at 300r / min at 45℃ for 120min. Turn on the circulating water cooling during the ball milling process.
[0085] Step (4): Fix the semi-cured impregnated sheet obtained in step (2) of Example 4 onto the carrier film, and use a five-roll coating unit to coat the ceramic precursor adhesive onto the surface of the semi-cured impregnated sheet. The coating thickness on one side is 10 μm. After coating, it is dried in an oven at a temperature of 105°C for 2.5 h, and then cooled in a cooling section for 25 min.
[0086] Step (5): Nine impregnated sheets obtained in step (4) of Example 4 are stacked as basic units, and then 35μm electrolytic copper foil is placed on the top and bottom layers. Vacuum pressing is performed in a high-temperature laminator. The pressing conditions are hot pressing at 240℃ and 1000psi for 4 hours.
[0087] Example 5:
[0088] Step (1): Prepare the impregnation sheet solution according to the components specified in Example 5 in Table 1 and the process flow: First, 0.01 parts of coupling agent Z-6124 and 0.03 parts of coupling agent Z-6030 are pretreated with 0.5 parts of hydrolytic solvent and then added to a planetary ball mill with 10 parts of alumina (D50=15μm) and 15 parts of rutile titanium dioxide. The mixture is ball-milled at 85°C for 1.5h to obtain the filler premix.
[0089] Then, 20 parts of butadiene resin, 80 parts of pentadiene compound resin, 10 parts of ethylene propylene diene copolymer, 20 parts of thermoplastic polyurethane and 100 parts of impregnated sheet were added to a high-shear stirring tank with solvent (water: ethanol = 8:2) and stirred at 300 r / min and 75°C for 4.5 h to obtain resin premix.
[0090] Mix the filler premix with the resin premix, add 10 parts of polybutadiene liquid rubber, 15 parts of EPDM liquid rubber, 5 parts of peroxide initiator and 10 parts of additives, and stir at 90℃ and 700r / min for 90min, with vacuum degassing mode activated during the process.
[0091] Step (2): Transfer the impregnating sheet adhesive solution into the tank, with ultrasonic dispersion at the bottom of the tank. Impregnate 1067 fiberglass cloth in a uniform adhesive solution with a mass concentration of 65% under vacuum-assisted conditions, repeating the impregnation three times to adjust to the predetermined thickness. Dry the impregnated fiberglass cloth at 125℃ for 4 minutes to remove low-temperature volatiles and form a semi-cured state. Then, cut and repackage the semi-cured roll of impregnated sheet.
[0092] Step (3): Prepare the adhesive layer solution according to the components specified in Example 5 in Table 1: Add 20 parts of polyvinylsilazane, 20 parts of block copolymer modified polysilazane, 10 parts of boron carbide (D50=1μm), 20 parts of silicon oxide (D50=2μm), 0.1 parts of coupling agent Z-6040, 0.5 parts of coupling agent Z-6030, 1 part of dicumyl peroxide, 1 part of ethylene dithiol, and 90 parts of xylene to a planetary ball mill. Run the mill at 55°C and rotate alternately in both forward and reverse directions at a speed of 280r / min for 90min. Turn on the circulating water cooling during the ball milling process.
[0093] Step (4): Fix the semi-cured impregnated sheet obtained in step (2) of Example 5 onto the carrier film, and use a five-roll coating unit to coat the ceramic precursor adhesive onto the surface of the semi-cured impregnated sheet. The coating thickness on one side is 7 μm. After coating, it is processed in a drying oven with the oven temperature set to 95°C and the processing time being 1.5 h. Then, it is cooled in a cooling section for 15 min.
[0094] Step (5): Eight impregnated sheets obtained in step (4) of Example 5 are stacked as basic units, and then 35μm electrolytic copper foil is placed on the top and bottom layers. Vacuum pressing is performed in a high-temperature laminator. The pressing conditions are hot pressing at 230℃ and 950psi for 3.5h.
[0095]
[0096]
[0097] The performance of the embodiments is shown in Table 2:
[0098]
[0099] The dielectric constants of the products in the examples range from 3.30 to 3.41, significantly lower than those of the commercial comparative example RO4350B. Example 1 exhibits a better dielectric constant than comparative example R-5775, while the other examples are close to R-5775. A lower dielectric constant means faster signal propagation within the material, better suited to the needs of high-frequency applications such as 5G and millimeter waves, and reduces signal latency. Under 150°C testing conditions, the dielectric loss of the products in the examples ranges from 0.0031 to 0.0038, more than 15% lower than RO4350B. Most examples outperform or match R-5775, indicating lower energy loss during signal transmission. This significantly improves the signal-to-noise ratio and transmission efficiency of the devices, resulting in a substantial performance improvement for devices such as high-frequency radar and antennas. Within the 150–300°C range, the dielectric constant temperature coefficient of the product in this embodiment is 44–46 ppm / °C, which is superior to RO4350B and comparable to R-5775. This indicates that the dielectric performance changes less with temperature, demonstrating that the product in this embodiment exhibits more stable dielectric performance at high temperatures and will not experience performance drift due to temperature increases, perfectly suited for the high-temperature operating scenarios of high-power devices. Peel strength is the adhesion between the metal foil and the dielectric substrate. The product in this embodiment shows a more than 5-fold improvement over the two commercial comparison samples, meaning extremely strong adhesion to the circuit board pads and traces, preventing pad detachment and trace fall-off during soldering and processing. The maximum continuous operating temperature of the product in this embodiment can reach 255-288℃, which is more than 55℃ higher than the two commercial products. Ordinary dielectric boards can only operate continuously below 200℃, while the products in this solution can operate continuously at high temperatures above 250℃. The maximum continuous operating temperature of embodiments 4 and 5 can reach 288℃, which perfectly solves the pain points of heat dissipation and high temperature resistance of high-power TR chips and highly integrated devices, allowing the devices to work stably in harsher high-temperature environments. The pencil hardness can be ≥6H, giving the products in this embodiment high strength and high hardness, making it easier to maintain dimensional integrity during use.
[0100] This invention prepares a low-cost, high-heat-resistant microwave composite dielectric board by coating a ceramic precursor adhesive layer onto a diene resin impregnated sheet. The unique heat resistance of the ceramic precursor overcomes the shortcomings of existing diene resin-based microwave composite dielectric boards, such as large dielectric loss variations at high temperatures and low heat resistance temperatures. This provides a microwave composite dielectric board with a low dielectric constant, stable dielectric properties, high adhesion to pads and circuits, and high-temperature resistance. This process is simple, efficient, and environmentally friendly, providing a novel manufacturing process for microwave composite dielectric boards used in electronic warfare, millimeter-wave radar, and automotive fields.
Claims
1. A method for preparing a low-cost, high-heat-resistant microwave composite dielectric substrate, characterized in that, Includes the following steps: S1: Preparation of semi-cured impregnated sheets based on diene resin; S2: A ceramic precursor adhesive is coated on the surface of the semi-cured impregnated sheet to form an adhesive layer; S3: Stack the coated impregnated sheets; S4: Place metal foils on the top and bottom layers after stacking, and vacuum press them in a high-temperature laminator to obtain a microwave composite dielectric board.
2. The method for preparing a low-cost, high-heat-resistant microwave composite dielectric substrate according to claim 1, characterized in that, In step S1, the method for preparing the semi-cured impregnated sheet includes: S11: Mix the raw materials for impregnating sheet solution in a high-shear mixing tank according to the specified proportion; S12: The impregnating sheet adhesive obtained in S11 is mixed with electronic fiberglass cloth in a gluing machine to form a continuous roll of impregnating sheet, and then dried to form a roll of semi-cured impregnating sheet. S13: Cut the roll of the semi-cured impregnated sheet obtained in S12 into impregnated single sheets that match the size of the microwave composite dielectric plate.
3. The method for preparing a low-cost, high-heat-resistant microwave composite dielectric substrate according to claim 2, characterized in that, In step S11, the impregnation sheet adhesive is made from the following raw materials in parts by weight: 100 parts diene resin, 10-60 parts thermoplastic elastomer toughening resin, 10-40 parts liquid toughening agent, 20-70 parts ceramic filler, 0.01-1.5 parts coupling agent, 0.05-5 parts hydrolyzed solvent, 0.5-6 parts curing agent for impregnation sheets, 0.5-20 parts additives, and 50-200 parts solvent for impregnation sheets.
4. The method for preparing a low-cost, high-heat-resistant microwave composite dielectric substrate according to claim 3, characterized in that, The diene resin is one or more of butadiene resin, pentadiene resin, isoprene resin, and hexadiene resin; The thermoplastic elastomer toughening resin is one or more of styrene-butadiene copolymer, styrene-isoprene copolymer, ethylene propylene diene monomer copolymer, and thermoplastic polyurethane; The liquid toughening agent is one or more of polyurethane liquid rubber, polybutadiene liquid rubber, isoprene liquid rubber and EPDM liquid rubber. The ceramic filler is one or more of the following: crystalline silica, fused silica, spherical silica, hollow microsphere silica, rutile titanium dioxide, anatase titanium dioxide, hollow microsphere titanium dioxide, alumina, hollow microsphere alumina, and hollow microsphere aluminum nitride; the median particle size of the ceramic filler is 10 μm to 30 μm. The coupling agent is one or more of Z-6040, Z-6124, Z-6030 and KH550 in combination; The curing agent for the impregnated sheet is one or more of peroxide initiators, vulcanizing crosslinking agents and triallyl cyanurate crosslinking agents; The solvent used for the impregnated sheet is one or more of the following: water, 1,2-propanediol, dichloromethane, ethanol, xylene, and cyclohexane.
5. The method for preparing a low-cost, high-heat-resistant microwave composite dielectric board according to claim 3, characterized in that, The specific steps of S11 are as follows: S111: After the coupling agent is pretreated with a hydrolytic solvent, the ceramic filler and the hydrolyzed coupling agent are added to a planetary ball mill in proportion and ball-milled at 60℃~90℃ for 1h~2h. The mixture is then removed and set aside for use. S112: Diolefin resin, thermoplastic elastomer toughening resin and impregnated sheet are added to a high-shear stirring tank with solvent, and stirred for 3 to 6 hours at a temperature of 50℃~90℃ and a stirring speed of 100r / min~600r / min. The mixture is then removed and set aside for use. Add the products of S111 and S112 to a high-shear mixing vessel, and then add liquid toughening agent, curing agent and additives in proportion. The mixing temperature is 60℃~95℃, the mixing speed is 100r / min~1000r / min, and the mixing time is 50min~180min. During the process, the vacuum degassing mode is turned on.
6. The method for preparing a low-cost, high-heat-resistant microwave composite dielectric substrate according to claim 2, characterized in that, The specific steps of S12 are as follows: S121: The electronic fiberglass cloth is impregnated in the impregnation solution after S11 treatment under vacuum-assisted conditions. The mass concentration of the solution is 10% to 80%. The impregnation is repeated 2 to 5 times, and the thickness is adjusted to the predetermined thickness according to the type of electronic fiberglass cloth. S122: Dry the impregnated electronic fiberglass cloth at 100-150℃ for 2-5 minutes to remove low-temperature volatiles and form a semi-cured state, thus obtaining the roll of the semi-cured impregnated sheet.
7. The method for preparing a low-cost, high-heat-resistant microwave composite dielectric substrate according to claim 6, characterized in that, The electronic fiberglass cloth is one of 106, 1080, 1067, 2116 and 7628 electronic grade low dielectric alkali-free fiberglass cloth, and the thickness of the electronic fiberglass cloth is less than 0.03 mm.
8. The method for preparing a low-cost, high-heat-resistant microwave composite dielectric substrate according to claim 1, characterized in that, In step S2, the specific operation of coating the ceramic precursor adhesive to form the bonding layer is as follows: a five-roller coating unit is used to coat the film, and the thickness of the bonding layer coated on one side is 5μm to 13μm; after coating, the impregnated sheet is treated in a drying oven at 80℃ to 110℃ for 0.5 to 3 hours, and then cooled for 10 minutes to 30 minutes.
9. The method for preparing a low-cost, high-heat-resistant microwave composite dielectric substrate according to claim 8, characterized in that, The ceramic precursor adhesive is made from the following raw materials in parts by weight: 100 parts of ceramic precursor and its modified resin, 0.5 to 2 parts of curing agent for adhesive layer, 60 to 250 parts of solvent for adhesive layer, 10 to 60 parts of ceramic microspheres and 0.1 to 1.5 parts of surface modifier; The ceramic precursor and its modified resin are one or more of the following: perhydropolysilazane, polyvinylsilazane, and block copolymer modified polysilazane; The ceramic microspheres are one or more of silicon carbide, boron carbide and silicon oxide; the median particle size of the ceramic microspheres is 0.5 μm to 2 μm. The surface modifier is one or more of Z-6040, Z-6124 and Z-6030 in combination; The curing agent for the adhesive layer is one or more of toluene diisocyanate, dicumyl peroxide, and ethylene dithiol; The solvent used in the adhesive layer is one or more of the following: hexane, toluene, xylene, dichloromethane, butanone, tetrahydrofuran, cyclohexane, 1,2-propanediol, and bromophenyl ether.
10. The method for preparing a low-cost, high-heat-resistant microwave composite dielectric substrate according to claim 9, characterized in that, The preparation method of the ceramic precursor adhesive is as follows: the ceramic precursor and its modified resin, the curing agent for the adhesive layer and the solvent for the adhesive layer are added to a planetary ball mill in proportion, and the mill is run alternately in forward and reverse directions at a speed of 200 r / min to 350 r / min at 40℃ to 60℃ for 30 min to 180 min. During the ball milling process, the circulating water cooling is turned on.